The Effectiveness of Using Edmodo as an Online Learning Platform in Covid-19 - Nur Ihsan Halil (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2020)
This study aimed to describe the effectiveness of using Edmodo, as one of the online learning platforms, in the lecture process at the Faculty of Teacher Training and Education of the Universitas Sembilanbelas November Kolaka (USN Kolaka). A sample of 124 students from a total of 1,606 FKIP students of USN Kolaka participated in this study by filling out questionnaires distributed online. Student responses were analyzed descriptively quantitatively to determine the effectiveness of the implementation of learning, in terms of two aspects (the level of student participation, and the attitude of students towards the implementation of lectures). The results of data analysis showed that online learning using Edmodo at FKIP USN Kolaka has been carried out effectively. The effectiveness of using Edmodo is due to its practicality (simple display, provides various features, and supports various file types), as well as the accessibility of its use (accessible even though the connection is unstable, and saves internet quota). The convenience provided by Edmodo platform is able to increase the average participation rate of students in online learning to reach 89.18%.